Fifteen-millimeter Stafne defect in the anterior mandible: Diagnostic contribution of multislice computed tomography - Bispo, Mayara Simões; Carneiro-Júnior, Bráulio; Souza, André Sampaio; Neves, Frederico Sampaio; Rossi, Marcelle Alvarez; Crusoé-Rebello, Iêda (Journal of Oral Diagnosis, 2019)
A Stafne bone defect is a cavity in the mandible. There is controversy regarding the cause of this defect, but imaging findings offer important diagnostic contributions. The aim of this report is to present the tomographic findings of a rare case of an extensive bone defect in the anterior mandible. A 55-year-old man was seen at a dental service for oral rehabilitation with dental implants. He was asymptomatic. Panoramic radiography revealed an oval, delimited radiolucency of cystic and regular appearance encompassing the area from the apex of tooth 26 to tooth 29; the major axis was parallel to the base of the mandible. Multislice computed tomography showed a cavity with heterogeneous content and the following measurements: buccal-lingual width/depth, 1.0 cm; anteroposterior width, 1.38 cm; height, 1.54 cm; area, 0.94 cm²; volume, 2.14 cm3; and attenuation coefficient ± standard deviation, 19.86±91.27 HU. These data confirmed the diagnosis of an anterior variant of Stafne bone defect. The size of a Stafne bone defect needs to be considered when planning implant-supported rehabilitation and other interventions in the affected area. Recognition and definitive diagnosis of this condition are essential, particularly with increasing use of rehabilitation treatments with osseointegrated implants.